Analysis of The Application of Giving Rewards to Improving Social Science Learning Outcomes For Elementary School Students - Yofita Sari; Waluyo Hadi; Nur Syadida Ramadhani (STKIP Taman Siswa Bima, 2024)
Education remains linked to human life, using experiences that provide understanding and insight to develop. Giving rewards is one of the educational tools used to improve student learning outcomes in class. The goal of the reward system is to make students more attentive and focused during lessons. Good intentions towards IPAS can encourage students to study in order to obtain good learning results. It is hoped that giving rewards can be used as a strategy to improve student learning outcomes in science courses. This research uses literature study or field work as an investigative method. The data used in this research comes from the results of analysis of several articles, journals, books and articles related to research variables. In addition, this research uses a descriptive-analytic approach to examine the relationship between the learning outcomes of science and science students in basic education and the award system through a review of previous research publications. According to this research, a consistent reward system can improve student learning outcomes in science and technology subjects in elementary schools.